Interconnections in the Ancient Near East. A Study of the Relationships between the Arts of Egypt, the Aegean, and Western Asia - Smith, William Stevenson (1965)
on unnumbered plates, 3 maps; published 1966; espec. Part I: Historical Survey of Interconnections; Part II, Ch. 6: Palace Decoration in Western Asia; 126s.